Meningkatkan Pemahaman Terhadap Soal Hots Matematika Sekolah Dasar Berdasarkan Pendekatan Numerasi (Study Literatur) (Jurnal Arjuna : Publikasi Ilmu Pendidikan, Bahasa dan Matematika, 2025)
This study aims to examine effective learning strategies in improving elementary school students' understanding of Higher Order Thinking Skills (HOTS) mathematics questions through a numeracy approach. The numeracy approach is an ability that not only involves numeracy skills, but also understanding and applying mathematical concepts in the context of everyday life so that students can think critically, analytically, and creatively. The method used in this study is a literature study that examines various scientific sources related to the application of numeracy and the development of HOTS in mathematics learning at the elementary school level. The results of the study indicate that learning strategies such as problem-based learning, Indonesian Realistic Mathematics Education (PMRI), collaborative learning, the use of interactive media, and integrated numeracy formative assessments are very effective in helping students master HOTS questions. In addition, the development of metacognitive abilities and adjusting strategies to student characteristics are also important factors for successful learning. The numeracy approach that links mathematical concepts to real contexts can increase students' learning motivation and active involvement so that understanding of HOTS questions can increase significantly. This study recommends that teachers integrate the numeracy approach in the planning and implementation of mathematics learning in order to produce meaningful learning that is oriented towards the development of students' high-order thinking skills.